Uptake and cytotoxicity of citrate-coated gold nanospheres: Comparative studies on human endothelial and epithelial cells - Freese, Christian (BioMed Central, 2012)
BACKGROUND: The use of gold nanoparticles (AuNPs) for diagnostic applications and for drug and gene-delivery is currently under intensive investigation. For such applications, biocompatibility and the absence of cytotoxicity of AuNPs is essential. Although generally considered as highly biocompatible, previous in vitro studies have shown that cytotoxicity of AuNPs in certain human epithelial cells was observed. In particular, the degree of purification of AuNPs (presence of sodium citrate residues on the particles) was shown to affect the proliferation and induce cytotoxicity in these cells. To expand these studies, we have examined if the effects are related to nanoparticle size (10, 11 nm, 25 nm), to the presence of sodium citrate on the particles' surface or they are due to a varying degree of internalization of the AuNPs. Since two cell types are present in the major barriers to the outside in the human body, we have also included endothelial cells from the vasculature and blood brain barrier. RESULTS: Transmission electron microscopy demonstrates that the internalized gold nanoparticles are located within vesicles. Increased cytotoxicity was observed after exposure to AuNPs and was found to be concentration-dependent. In addition, cell viability and the proliferation of both endothelial cells decreased after exposure to gold nanoparticles, especially at high concentrations. Moreover, in contrast to the size of the particles (10 nm, 11 nm, 25 nm), the presence of sodium citrate on the nanoparticle surface appeared to enhance these effects. The effects on microvascular endothelial cells from blood vessels were slightly enhanced compared to the effects on brain-derived endothelial cells. A quantification of AuNPs within cells by ICP-AES showed that epithelial cells internalized a higher quantity of AuNPs compared to endothelial cells and that the quantity of uptake is not correlated with the amount of sodium citrate on the nanoparticles’ surface. CONCLUSIONS: In conclusion the higher amount of citrate on the particle surface resulted in a higher impairment of cell viability, but did not enhance or reduce the uptake behavior in endothelial or epithelial cells. In addition, epithelial and endothelial cells exhibited different uptake behaviors for citrate-stabilized gold nanoparticles, which might be related to different interactions occurring at the nanoparticle-cell-surface interface. The different uptake in epithelial cells might explain the higher reduction of proliferation of these cells after exposure to AuNPs treatment although more detailed investigations are necessary to determine subcellular events. Nevertheless an extrinsic effect of sodium-citrate stabilized particles could not be excluded. Thus, the amount of sodium citrate should be reduced to a level on which the stability of the particles and the safety for biomedical applications are guaranteed.